Trace Elements in Muscovite as a Guide to Gem Tourmaline Bearing Pegmatites in Nepal - Einfalt, H. C.; Kaphle, K. P.; Joshi, P. R. (Journal of Nepal Geological Society, 1995)
The pegmatites of Hyakule, and to a lesser extent, of Phakuwa area. Sankhuwa Sabha district. Eastern Nepal, have been a source for gem quality tourmaline since about 60 years. Only 4 pegmatite bodies, 2 each in Hyakule and Phakuwa, out of about 40 dikes altogether, yielded this precious stones despite at least 5 larger openings and probably some smaller ones in other dikes.The Phakuwa and Hyakule area occupies the eastern limb of the Arun anticline and consists of high grade metamorphic rocks of possibly Precambrian age belonging to the basal part of the Higher Himalayan crystalline. These rocks thrust south ward along the Main Central Thrust over the rocks of the Nawakot complex belonging to the Lesser Himalaya.The metamorphic sequence, about 2500 m thick, consists mainly of gneisses, garnet-kyanite and game-staurolite mica schist, quartzites and marbles with intercalated minor calc-silicate rocks. Pegmatites occur in the mica schist and interbedded calc-silicate schist sequence (approximately 1000 m thick) as scattered lenses or possibly dikes of a few min thickness, which cut discordantly through the host rocks. Internal zoning has developed generally into an upper blocky feldspar zone, a central quartz core with tourmaline and beryl (partly as aquamarine) and a lower fine grained, garnet bearing muscovite-quartz feldspar zone. Schorl is quite frequent as is biotite, the latter is often more abundant than muscovite. Uraninite and Ta-Nb minerals (tantalite, wodginile, pyrochlore) as well as cassiterite have been found in heavy mineral concentrates of a few investigated pegmatite samples.The current paper deals with several questions: what is the type of these pegmatites in terms of a classification? Do all pegmatites belong to the same generation and/or stage of evolution? Why are gem quality tourmalines known only from a few dikes? Is there an exploration method to distinguish between barren and gem tourmaline pegmatites in these areas? Could this method possibly be applied to other pegmatite areas in Nepal?We used trace and some major element characteristics of 24 coarse grained muscovite samples from 19 pegmatite dikes in Phakuwa and Hyakule and from localities nearby to answer these questions. Additional 4 muscovite samples from gem tourmaline   bearing   and   barren   pegmatites   in   the    Ilam   district    have   been    included    for   comparison. The trace element characteristics, some main elements and some element ratios of coarse grained muscovites in Hyakule and Phakuwa distinguish clearly between a group of gem producing and barren pegmatites. The most powerful distinguishing geochemical features are the concentration ranges of Rb, Ba, MnO and MgO and the element ratios K/Rb and Li/Mg. Less useful are the concentrations of Cs, Sn and Ta because of a somewhat irregular behaviour. Surprisingly, Li is rather low in all samples and does not discriminate very distinctly between the two pegmatite groups. The results of this study can probably be used as a rapid exploration tool in sorting out barren pegmatites from pegmatites with a potential for gem quality tourmaline.